The Speaker of the National Assembly: ways to strengthen and enhance the independence of the Speaker's office - Graham, Wesley (Department of Public Law, 2016)
The main intention of this paper is to ascertain whether the Speakership and Parliament are involved in a symbiotic relationship. This paper will assess whether a weak incumbent will have an adverse effect on the NA thereby weakening the capacity of the NA itself.